Α‐Angelica Lactone Catalyzed Oxidation of Pyrrolidines to Lactams. Issue 31 (16th August 2022) - Deepake, Siddharth K.; Kumar, Manish; Kumar, Pawan; Das, Utpal
Abstract: Herein, we report an efficient protocol for the synthesis of γ‐lactams from pyrrolidines and oxygen. The strategy follows a two‐step process involving an initial generation α‐amino alkyl radicals from pyrrolidines and oxygen in presence of 4‐dimethylaminopyridine (DMAP) followed by trapping of the radical with oxygen species. This protocol demonstrates good functional group acceptance and provides a direct method to access γ‐lactams. The lactam derivatives were obtained in up to 98 % yield. Abstract : An efficient method for the direct oxidation of various N‐aryl pyrrolidines to the corresponding lactams using α‐ angelica lactone as catalyst has been demonstrated. Di‐oxygen was employed as the terminal oxidant and oxygen source.